Marketing Portfolio in Managing Uncertainty Risk During the Covid-19 Pandemic - Ari Wijaya, Oscarius Yudhi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Apart from finance and accounting, marketing is an important aspect that determines the level of success in managing a business or company. The entrepreneurial marketing concept revolutionize marketing strategies rather than relying on approaches that have been used for long, especially by large companies. This study examines marketing as a management strategy. It focuses on the role of entrepreneurial marketing in marketing strategies and how it works in various companies when faced with market uncertainty risk. Marketing strategy is associated with risk management theory, including dealing with crisis due to a pandemic. Building a marketing concept to anticipate market uncertainty is not difficult provided it does not conflict with other key factors in entrepreneurial management. Entrepreneurial marketing is a common approach used by small businesses, though established companies utilize large media. In case of a pandemic, marketing proportionally combines the entrepreneurial and traditional approaches depending on uncertainties. This study shows that using different marketing strategies is still not sufficient to avoid uncertainty during a pandemic. The main solution in this regard should involve increasing purchasing power through social assistance and restoring people's mobility while limiting the risk of spreading Covid-19. Keywords: Entrepreneurial Marketing, Marketing Portfolio, Risk Management, Covid-19